Determination of ratio of unsaturated to total fatty acids in edible oils by laser Raman spectroscopy - Farhad, S. Farid Uddin; Abedin, K.M.; Islam, M. Rafiqul; Talukder, Aminul I.; Haider, A F M Yusuf (© 2009 Asian Network for Scientific Information, 2017)
This article was published in the Journal of Applied Sciences [© 2009 Asian Network for Scientific Information] and the definite version is available at: 10.3923/jas.2009.1538.1543